2019
DOI: 10.3390/jcm8111886
|View full text |Cite
|
Sign up to set email alerts
|

Myorelaxant Effect of Transdermal Cannabidiol Application in Patients with TMD: A Randomized, Double-Blind Trial

Abstract: (1) Background: The healing properties of cannabidiol (CBD) have been known for centuries. In this study, we aimed to evaluate the efficiency of the myorelaxant effect of CBD after the transdermal application in patients with myofascial pain. (2) Methods: The Polish version of the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD Ia and Ib) was used. A total of 60 patients were enrolled in the study and were randomly divided into two groups: Group1 and Group2. The average age in Group1 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 41 publications
0
56
0
4
Order By: Relevance
“…One study reported myorelaxant effects with significant reduction in pain scores among 30 patients with temporomandibular disorders who were administered CBD containing hemp-based cholesterol ointment, compared to controls. Small sample size and unspecified amount of dose administered are among the important limitations of this study [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study reported myorelaxant effects with significant reduction in pain scores among 30 patients with temporomandibular disorders who were administered CBD containing hemp-based cholesterol ointment, compared to controls. Small sample size and unspecified amount of dose administered are among the important limitations of this study [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the 18 clinical trials included, adverse reactions reported for CBD, hemp products and MaZiRenWan are generally tolerable with no permanent disabling effects, though these may have contributed towards drop outs in some studies (up to 30%) [ 26 , 31 , 32 , 34 , 35 , 43 , 44 , 48 , 49 , 51 53 , 56 , 57 , 64 , 75 , 77 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although oral consumption of oils or edible forms of hemp extract is used across species (Birnbaum et al., 2019; Gamble et al., 2018; McGrath et al., 2019; Taylor, Gidal, Blakey, Tayo, & Morrison, 2018), in veterinary medicine transdermal approaches are sought to ease delivery and prevent negative relationships between the owner and animal. There are limited data on the use of transdermal delivery of CBD and THC; however, preclinical models and human data suggest ample delivery of CBD and/or THC can be achieved (Bruni et al., 2018; Hammell et al., 2016; Hu, Cullen, Tang, & Fang, 2020; Lodzki et al., 2003; Niteckta‐Buchta et al, 2019). Recently, a publication in dogs suggested that steady‐state serum concentration of CBD is around 100–200 ng/ml when providing 10–20 mg/kg of an undisclosed transdermal form of CBD‐rich hemp extract twice daily, suggesting dermal absorption of CBD (Bartner, McGrath, Rao, Hyatt, & Wittenburg, 2018); however, aural erythema was a common side effect of the treatment which may be due to the ointment formulation (McGrath, Bartner, Rao, Kogan, & Hellyer, 2018).…”
Section: Figurementioning
confidence: 99%
“…The use of transdermal applications of hemp‐derived cannabinoids has been proven to be effective in clinical and preclinical models and human studies in temporomandibular joint disease and peripheral neuropathic pain (Hu et al, 2020; Niteckta‐Buchta et al, 2019). The exact mechanisms of action related to CBD and associated cannabinoids effects on pain and whether these effects are through systemic or local effects on pain are unclear; however, similar findings related to mitigation of pain have been observed in preclinical rodent models examining the effects of cannabidiol on models of osteoarthritis and dermatitis (Bruni et al., 2018; Hammell et al., 2016; Lodzki et al., 2003).…”
Section: Figurementioning
confidence: 99%